TRANSFORMASI SPASIAL PADA KORIDOR RUANG JALAN CENDRAWASIH – DEMANGAN BARU YOGYAKARTA - Marchelia Dwi Rikatyani; Dyah Titisari Widyastuti (Pawon: Jurnal Arsitektur, 2022)
Spatial transformation in corridors road space is a shape transformation of the road space structure and shape from the previous condition to the current condition, including physical and non-physical spaces, namely roads and the scope of road space as a form of a spatial structure. The Cendrawasih – Demangan Baru corridor road space has a strategic location, which is in Depok District as the center of education and economy in Sleman Regency and it is directly next to the Yogyakarta city. It has a direct impact on the Cendrawasih – Demangan Baru corridor road space so it be through a spatial transformation due to the increase of commercial activity in this area. This study used a qualitative rationalistic method with comparative descriptive analysis. This study examined the spatial transformation of the Cendrawasih – Demangan Baru corridor road space from 2006 to 2021 by combining field observations, interviews, and literature studies. Based on the analysis and theoretical study results, there was a significant transformation in the scope of the road space which included a partial transformation to a total transformation, while the roads and pedestrian paths had not changed in their dimensions, but both of them could not fulfill the needs of road space users due to the transformation in the road space scope. The factors causing the transformation were function transformation, ownership transformation and building transformation.